Investigation of the Uptake and Transport of Aspirin Eugenol Ester in the Caco-2 Cell Model - Tao, Qi; Qin, Zhe; Liu, Xi-Wang; Zhang, Zhen-Dong; Li, Shi-Hong; Bai, Li-Xia; Li, Jian-Yong; Yang, Ya-Jun (Frontiers in Pharmacology, 2022)
Background: Aspirin eugenol ester (AEE) is a new medicinal compound synthesized by esterification of aspirin with eugenol using the prodrug principle. AEE has anti-inflammatory, antipyretic, analgesic, anti-cardiovascular diseases, and anti-oxidative stress pharmacological activity. However, its oral bioavailability is poor, and its intestinal absorption and transport characteristics are still unknown. Objective: The purpose of this study was to investigate the uptake and transport mechanisms of AEE in Caco-2 cells. Methods: The effects of time, concentration, and temperature on the transport and uptake of AEE were studied. Results: The results showed that higher concentration of salicylic acid (SA) was detected in the supernatant of cell lysates and cell culture medium, while AEE was not detected. Therefore, the content change of AEE was expressed as the content change of its metabolite SA. In the uptake experiment, when the factors of time, concentration, and temperature were examined, the uptake of SA reached the maximum within 30 min, and there was a concentration dependence. In addition, low temperature (4℃) could significantly reduce the uptake of SA in Caco-2 cells. In the transport experiment, under the consideration of time, concentration, and temperature, the transepithelial transport of SA from AP-BL and BL-AP sides was time-dependent. The amount of SA transported in Caco-2 cells increased with the increase of concentration, but the transmembrane transport rate had no correlation with the concentration. This phenomenon may be due to the saturation phenomenon of high concentration. The efflux ratio (ER) was less than 1, which indicated that their intestinal transport mechanism was passive transport. Moreover, the temperature had a significant effect on the transport of AEE. Conclusion: In summary, intestinal absorption of AEE through Caco-2 cell monolayers was related to passive transport. The uptake and transport of AEE were concentration-dependent, and temperature significantly affected their uptake and transport. The absorption and transport characteristics of AEE may contribute to the exploration of mechanisms of absorption and transport of chemosynthetic drugs in vitro.